Hollywood Zen: A Historical Analysis of Oshima Nagisa’s Unfinished Film - Daisuke Miyao (Mise au Point)
In this essay, I consider Oshima Nagisa’s unmade film, Hollywood Zen, to be his historical project. Throughout his career as a filmmaker, Oshima kept questioning the modernized feudal patriarchy of the emperor system after the Meiji Restoration that led to the devastation of World War II, oppression toward women and minority groups, and the immorality of the Meiji generation for its subjugation to ultranationalism and fascism during wartime as well as its instant switch to American-style democracy during the post-WWII occupational period. Closely examining the screenplay of Hollywood Zen, which Oshima wrote with Paul Mayersberg, in conjunction with articles written in the 1910s-20s in both American and Japanese trade presses and film magazines, I discuss the politics of representation of race as well as the politics of gender embodied by the stardom of Sessue Hayakawa in the 1910s in different national contexts. I will clarify how the “New Wave” filmmaker who started his career in postwar Japan critically tried to represent the beginning of the star system in Hollywood.